Rozwiaz rownania:
a.
7x+14=5x-22
b.
-3+2x-6=3-4x
c.
-2(x+3)+4(2x+3)=-6
d.
-(x+3)+(2x-1)=1+4x+(3+x)
e.
-(4-2x)-(2x+4)=(3x-1)+(2x+5)-(7-3x)
f.
2(2x-3)+3(4-x)=-(x+1)
g.
3(3-x)+2x=8-2(x-1)
h.
4x+5-(3x+6)=2(2+x)-4

j.
2(x-3)+4=3x-1-(x+2)
k.
x-7+3(2-x)=½(2x-4)+5

Prosze o rozwiazanie:)

3

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-10T15:53:28+01:00
A.
7x+14=5x-22
2x=-36
x=-18
b.
-3+2x-6=3-4x
6x=12
x=2
c.
-2(x+3)+4(2x+3)=-6
-2x-6+8x+12=-6
6x=-12
x=-2
d.
-(x+3)+(2x-1)=1+4x+(3+x)
-x-3+2x-1=1+4x+3+x
-4x=8
x=-2
e.
-(4-2x)-(2x+4)=(3x-1)+(2x+5)-(7-3x)
-4+2x-2x-4=3x-1+2x+5-7+3x
-8x=5
x=-5/8
f.
2(2x-3)+3(4-x)=-(x+1)
4x-6+12-3x=-x-1
2x=-7
x=-7/2
x=-3,5
g.
3(3-x)+2x=8-2(x-1)
9-3x+2x=8-2x+2
x=1
h.
4x+5-(3x+6)=2(2+x)-4
4x+5-3x-6=4+2x-4
-x=1
x=-1
j.
2(x-3)+4=3x-1-(x+2)
2x-6+4=3x-1-x-2
nie ma rozwiązania
k.
x-7+3(2-x)=½(2x-4)+5
x-7+6-3x=x-2+5
-3x=4
x=-4/3
  • ZuZX
  • Rozwiązujący
2010-03-10T15:56:33+01:00
A.
7x+14=5x-22
7x-5x=22-14
2x=8
x=4

b.
-3+2x-6=3-4x
-3x+4x+2x=3+6
3x=9
x=3

c.
-2(x+3)+4(2x+3)=-6
-2x-6+8x+12=-6
4x+6 = -6
4x= 0
sprzeczne.

d.
-(x+3)+(2x-1)=1+4x+(3+x)
-x-3+2x-1=1+4x+3+x
x-4=5x+4
x-5x=4+4
-4x = 8
x = -2

e.
-(4-2x)-(2x+4)=(3x-1)+(2x+5)-(7-3x)
-4+2x-2x-4=3x-1+2x+5-7+3x
-8=8x-3
-8+3=8x
8x=-5
x= -⅝

f.
2(2x-3)+3(4-x)=-(x+1)
4x-6+12-3x=-x-1
x+6=-x-1
x+x=7
2x=7
x=3,5

g.
3(3-x)+2x=8-2(x-1)
9-3x+2x=8-2x+2
9-x=10-2x
x=1

h.
4x+5-(3x+6)=2(2+x)-4
4x+5-3x-6=4+2x-4
x+-1=2x
x=1

j.
2(x-3)+4=3x-1-(x+2)
2x-6+4=3x-1-x-2
2x-2=2x-3
2x-2x=-1
Sprzeczne.

k.
x-7+3(2-x)=½(2x-4)+5
x-7+6-3x=x-2+5
-2x-1=x+3
-1-3=x+2x
3x=-4
x= 1⅓
2010-03-10T16:04:09+01:00
A.
7x+14=5x-22
7x-5x=-22-14
2x=-36/÷2
x=-18
b.
-3+2x-6=3-4x
4x+2x=3+6+3
6x=12/÷6
x=2
c.
-2(x+3)+4(2x+3)=-6
-2x-6+8x+12=-6
6x=-6+6-12
6x=-12/÷6
x=-2
d.
-(x+3)+(2x-1)=1+4x+(3+x)
-x-3+2x-1=1+4x+3+x
-x+2x-4x-x=3+1+1+3
-4x=8/÷(-4)
x=-2
e.
-(4-2x)-(2x+4)=(3x-1)+(2x+5)-(7-3x)
-4+2x-2x-4=3x-1+2x+5-7+3x
2x-2x-3x-2x+3x=4+4-1+5-7
-2x=5/÷(-2)
x=-2,5
f.
2(2x-3)+3(4-x)=-(x+1)
4x-6+12-3x=-x+1
2x=6-12+1
2x=5/÷2
x=2,5
g.
3(3-x)+2x=8-2(x-1)
9-3x+2x=8-2x+2
-3x+2x+2x=-9+8+2
x=1
h.
4x+5-(3x+6)=2(2+x)-4
4x+5-3x-6=4+2x-4
4x-3x-2x=-5+6+4+4
-x=9/÷(-1)
x=-9
j.
2(x-3)+4=3x-1-(x+2)
2x-6+4=3x-1-x-2
2x-3x+x=6-4-1-2
0=-1
k.
x-7+3(2-x)=½(2x-4)+5
x-7+6-3x=x-2+5
x-3x-x=7-6-2+5
-3x=4/÷(-3)
x=-¾